2008
DOI: 10.1111/j.1582-4934.2008.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

AAA ATPase p97/VCP: cellular functions, disease and therapeutic potential

Abstract: p97/VCP, a member of the AAA-ATPase super family, has been associated with a wide variety of essential cellular protein pathways com prising: (i) nuclear envelope reconstruction, (ii) cell cycle, (iii) Golgi reassembly, (iv) suppression of apoptosis and (v) DNA-damage response [1-6]. In addition, vasolin-containing protein (VCP) dislodges the ubiquitinated proteins from the endoplasmic reticulum (ER) and chaperones them to the cytosol for proteasomal degradation by endoplasmic reticulum-associated degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 51 publications
2
94
0
Order By: Relevance
“…Therefore, the processing of MMTV and betaretrovirus SPs appears to be fundamentally different from other positive-stranded RNA viruses. Because defects in protein folding and ERAD are associated with many human diseases (26), further studies of betaretrovirus SP trafficking will continue to illuminate many important aspects of cell biology and pathogenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the processing of MMTV and betaretrovirus SPs appears to be fundamentally different from other positive-stranded RNA viruses. Because defects in protein folding and ERAD are associated with many human diseases (26), further studies of betaretrovirus SP trafficking will continue to illuminate many important aspects of cell biology and pathogenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been implicated in protein degradation via both the ubiquitin-proteasome and autophagy pathways, and in membrane fusion, transcriptional activation, apoptosis, and molecular chaperoning. [25][26][27][28] The 6 VCP mutations detected in this series are predominantly in the CDC48 substrate binding domain or the associated L1 linker between the CDC48 and D1 domains (figure 2). These residues are highly conserved across species; these mutations were predicted to be pathogenic by Pmut (http://mmb2.pcb.ub.es:8080/PMut/), with the exception of I114V, which was predicted to be neutral.…”
mentioning
confidence: 99%
“…Biochemical studies have shown that VAT unfolds globular proteins and interacts directly with the 20S core particle (CP) of the proteasome, leading to enhanced proteolytic activity for both folded and unfolded protein substrates (18)(19)(20)(21). In eukaryotes, the enzymes Cdc48 and p97/VCP, which are homologous to VAT, play essential roles in a large number of cellular functions, including transcriptional and metabolic regulation, cell cycle progression, membrane fusion, apoptosis, and protein degradation (22). Interestingly, eukaryotic analogs of VAT, such as Cdc48 and p97, lack critical Tyr residues in the pore loops of the D1 domain that are important for unfolding protein substrates and passing them into the lumen of the enzyme.…”
mentioning
confidence: 99%